A giant cell tumor of the bone in the rib cage left to proliferate unfettered for seven years to an extensive size. (2021) - Yang, Ellen; Li, Tianyang; Katz, Ariel
Abstract: Giant cell tumors of the bone are generally benign tumors of the bone, though they can be locally invasive in nature. They are also known as "osteoclastomas, " and patients are typically between 20 and 40 years of age, who present with pain and swelling of the joints. Though the tumor is benign, malignant degeneration, metastasis, and other complications of tumor growth are possible. Here we present a case where a delay in treatment led to a significant tumor burden. This tumor's unique location in the anterior arc of the rib, as well as its growth to a size that has rarely been reported, ultimately caused major compressive effects that significantly impacted our patient's quality of life. Highlights: Giant cell tumor of the bone can grow to colossal sizes. Tumors in the anterior ribs risk compression and compromise of thoracic structures. Early intervention in such diseases with aggressive growth is crucial. Access to wellness education and care is key to improving outcomes.